2012
DOI: 10.1186/1752-1947-6-136
|View full text |Cite
|
Sign up to set email alerts
|

A novel diagnostic sign of hip fracture mechanism in ground level falls: two case reports and review of the literature

Abstract: IntroductionMost elderly hip fractures are the result of a ground level fall. Defining high risk falls and fracture mechanisms are important to develop successful hip fracture prevention programs. This case series presents a previously unreported diagnostic sign and for the first time documents a hip fracture mechanism for a knee impact injury from a ground level fall in two elderly patients.Case presentationCase 1 was a 65-year-old Caucasian woman who fell forward with initial contact to her left knee, sustai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Noteworthy is the contextual use of the expression in situ . As is evident from the foregoing, this phrase can be used in oncology ( carcinoma in situ ), as well as in the process of measurement taking, viewing anatomical structures, and medical simulation (for example, “She was treated operatively with an in situ cannulated hip screw fixation and healed completely within eight weeks” [ 21 ]), depending on the context. Hence, this is one of the most productive Latin lexical units in modern medical discourse.…”
Section: Resultsmentioning
confidence: 99%
“…Noteworthy is the contextual use of the expression in situ . As is evident from the foregoing, this phrase can be used in oncology ( carcinoma in situ ), as well as in the process of measurement taking, viewing anatomical structures, and medical simulation (for example, “She was treated operatively with an in situ cannulated hip screw fixation and healed completely within eight weeks” [ 21 ]), depending on the context. Hence, this is one of the most productive Latin lexical units in modern medical discourse.…”
Section: Resultsmentioning
confidence: 99%
“…Whenever possible, we advocate that education programs enlist older adult peer educators and/or family to facilitate knowledge transfer and exchange. Notably, in 1 study, convincing residents about the positive effects of hip protectors became more difficult each time a hip fracture occurred while protected, 67 suggesting that it is especially important to inform caregivers, residents, and families that hip protectors cannot prevent fracture in all circumstances 42 (eg, in situations of spontaneous fracture without any obvious external impact, 84 when the hip breaks because of a backward fall or a fall to the knees, 85 or when the hip protector is not correctly positioned 86 ).…”
Section: Discussionmentioning
confidence: 98%
“…To test concurrent validity, we examined the ability of the two lower-order factors and the entire C-HiP Index to distinguish between subgroups of respondents that it should theoretically be able to distinguish between. Although hip protectors substantially reduce risk of hip fracture if worn during a fall, they cannot prevent hip fracture on every occasion, including cases of spontaneous fracture without any obvious external impact (e.g., [ 69 ]), when the hip breaks from impact to the buttocks during of a backwards landed fall or a fall to the knees (e.g., [ 22 , 70 ]), or when the hip protector is not positioned correctly over the greater trochanter (e.g., [ 71 , 72 ]). Forsen et al [ 73 ] reported that it became increasingly difficult to convince residents of the benefits of hip protectors after each time a hip fracture occurred while wearing a hip protector.…”
Section: Methodsmentioning
confidence: 99%